A New Use for an Old Drug: Carmofur Attenuates Lipopolysaccharide (LPS)-Induced Acute Lung Injury via Inhibition of FAAH and NAAA Activities - Wu, Kangni; Xiu, Yanghui; Zhou, Pan; Qiu, Yan; Li, Yuhang (Frontiers in Pharmacology, 2019)
Acute lung injury (ALI), characterized by a severe inflammatory process, is a complex syndrome that can lead to multisystem organ failure. Fatty acid amide hydrolase (FAAH) and N-acylethanolamine acid amidase (NAAA) are two potential therapeutic targets for inflammation related diseases. Herein, we identified carmofur, a 5-fluorouracil-releasing drug and clinically used as a chemotherapeutic agent, as a dual FAAH and NAAA inhibitor. In Raw264.7 macrophages, carmofur effectively reduced the mRNA expression of pro-inflammatory factors, including IL-1β, IL-6, iNOS and TNF-α, and down-regulated signaling proteins of the NF-κB pathway. Furthermore, carmofur significantly ameliorated the inflammatory responses, suppressed neutrophils infiltration and promoted resolution of pulmonary injury in lipopolysaccharides (LPS) induced ALI mice. The pharmacological effects of carmofur were partially blocked by peroxisome proliferator-activated receptor-α (PPARα) antagonist MK886 and cannabinoid receptor 2 (CB2) antagonist SR144528, indicating that carmofur attenuated LPS induced ALI in a PPARα and CB2 dependent mechanism. Our study suggested that carmofur might be a novel therapeutic agent for ALI, and drug repurposing may provide us effective therapeutic strategies for ALI.